Transforming growth factors: isolation of polypeptides from virally and chemically transformed cells by acid/ethanol extraction. - Roberts, A B (1980)
Polypeptides characterized by their ability to confer a transformed phenotype on an untransformed indicator cell have been isolated directly from tumor cells growing both in culture and in the animal, by using an acid/ethanol extraction procedure. Assay of these polypeptides is based on their ability to induce normal rat kidney fibroblasts to form colonies in soft agar. Peptides from murine sarcoma virus-transformed mouse 3T3 cells grown in culture had the highest specific activity in this assay; peptides from sarcomas produced from these cells or from chemically induced transplantable bladder carcinomas of mice were one-third as active; and peptides from a chemically induced rat tracheal carcinoma had only one-tenth the activity. Treatment with either trypsin or dithiothreitol destroyed the activity of all of these materials. The properties of these intracellular polypeptides from both virally and chemically transformed cells are similar to those described for the sarcoma growth factors (SGFs) previously isolated from the conditioned medium of sarcoma virus-transformed mouse 3T3 cells, suggesting the definition of a class of transforming growth factors common to tumor cells of different origins. The transforming peptides from the cultured sarcoma virus-infected cells were separately by gel filtration into two fractions of apparent molecular weight 7000 and 10,000. The major fraction at molecular weight 7000 represented approximately 0.1% of the original cell protein and had a specific activity 50 times that of the original acid/ethanol extract.